Short- and Long-Term, 11–22 Years, Results after Laparoscopic Nissen Fundoplication in Obese versus Nonobese Patients. (11th May 2017) - Schietroma, Mario; Piccione, Federica; Clementi, Marco; Cecilia, Emanuela Marina; Sista, Federico; Pessia, Beatrice; Carlei, Francesco; Guadagni, Stefano; Amicucci, Gianfranco
Abstract : Background . Some studies suggest that obesity is associated with a poor outcome after Laparoscopic Nissen Fundoplication (LNF), whereas others have not replicated these findings. The effect of body mass index (BMI) on the short- and long-term results of LNF is investigated. Methods . Inclusion criteria were only patients who undergone a LNF with at least 11-year follow-up data available, patients with preoperative weight and height data available for calculation of BMI (Kg/m 2 ), and patients with a BMI up to a maximum of 34.9. Results . 201 patients met the inclusion criteria: 43 (21.4%) had a normal BMI, 89 (44.2%) were overweight, and 69 (34.4%) were obese. The operation was significantly longer in obese patients; the use of drains and graft was less in the normal BMI group (p < 0.0001 ). The hospital stay, conversion (6, 4%), and intraoperative and early postoperative complications were not influenced by BMI. Conclusions . BMI does not influence short-term outcomes following LNF, but long-term control of reflux in obese patients is worse than in normal weight subjects.